Biomass Production and Carbon Sequestration of Mangium (Acacia mangium Willd.) Under Varying Plant Spacing - Routray, S. L.; Bhol, N.; Nayak, R. K.; Mohapatra, S. R. (Indian Forester, 2018)
The study on biomass production and carbon sequestration of Acacia mangium Willd. under varying plant spacing was conducted at College of Forestry, Orissa University of Agriculture and Technology (O.U.A.T), Bhubaneswar, India during 2013 – 2014 on 10 year old experimental plantation. The study explored a 10 year old A. mangium plantation embodying ten different spacing with the objective to find out the optimum spacing of A. mangium which is a fast growing NFT and popular now a days in agroforestry and farm forestry programmes. The biomass ranged from 106.84 to 131.46 t/ha, 19.84 to 34.27 t/ha, 22.58 to 30.28 t/ha and 42.96 to 48.97 t/ha in stem, branch, leaf and root, respectively. The total biomass varied from 192.2 to 244.91 t/ha. The overall biomass production was found to be maximum under S1(2m×1m) which was at par with S2, S3, S4, S5 and S6. The minimum values were observed under S10 with a parity of values with S9 and S6. The total biomass decreased with increase in spacing. The carbon sequestration ranged from 50.75 to 62.44, 9.42 to 16.27, 10.73 to 14.38 and 20.41 to 23.23 t/ha in stem, branch, leaf and root, respectively. The total carbon sequestration varied from 91.30 to 116.33 t/ha which decreased with increase in plant spacing. S showed highest value which 1 was at par with 2, S3, S4, S5 and S6 The S6 was found as optimum spacing. because among S to S spacing, cost of production was lowest in S due 1 6 6 to less number of pit preparation, less number of planting materials and also less cost of harvesting. Further, this spacing can provide scope for intercropping as A. mangium is a suitable tree species for agroforestry. Hence, S6 i.e 4m×2m was found to be the most suitable spacing among the ten different spacing tried.